Language Schools in Algeria -between Didactic and Social Factors - - بن ناصر إيمان; بوبكر جيملي (Milev Journal of Research and Studies, 2023)
The Language schools in Algeria are a socio-educational-linguistic phenomenon that has emerged since the beginning of the 2000s. This paper aims at a socio-educational analysis of the social factors that led to the emergence of this type of education, as well as the linguistic and educational requirements for it. We concluded that language schools are a socially constructed phenomenon based on the changes taking place in the structure of Algerian society, the emergence of the knowledge economy, social needs for employment, social transition, and the inability of the educational system to meet all the needs of learners. The actors in these schools adopt various linguistic and educational theories, according to the type of the educated groups and the goal of learning the foreign language.